[Afisz. Incipit:] Magia piosenki wykonawcy ... (Gdynia : [wydawca nieznany], 1966)
Afisz informujący o koncercie.
Keywords: Życie muzyczne -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne